Low levels of C‐peptide have clinical significance for established Type 1 diabetes. Issue 10 (16th August 2015) - Kuhtreiber, W. M.; Washer, S. L. L.; Hsu, E.; Zhao, M.; Reinhold, P.; Burger, D.; Zheng, H.; Faustman, D. L.
Abstract Aim To determine whether the low C‐peptide levels (< 50 pmol/l) produced by the pancreas for decades after onset of Type 1 diabetes have clinical significance. Methods We evaluated fasting C‐peptide levels, duration of disease and age of onset in a large cross‐sectional series (n = 1272) of people with Type 1 diabetes. We then expanded the scope of the study to include the relationship between C‐peptide and HbA1c control (n = 1273), as well as diabetic complications (n = 324) and presence of hypoglycaemia (n = 323). The full range of C‐peptide levels was also compared with 1, 5‐Anhydroglucitol, a glucose responsive marker. Results C‐peptide levels declined for decades after diagnosis, and the rate of decline was significantly related to age of onset (P < 0.0001), after adjusting for disease duration. C‐peptide levels > 10 pmol/l were associated with protection from complications (e.g. nephropathy, neuropathy, foot ulcers and retinopathy; P = 0.03). Low C‐peptide levels were associated with poor metabolic control measured by HbA1c (P < 0.0001). Severe hypoglycaemia was associated with the lowest C‐peptide levels compared with mild (P = 0.049) or moderate (P = 0.04) hypoglycaemia. All levels of measurable C‐peptide were responsive to acute fluctuations in blood glucose levels as assessed by 1, 5‐Anhydroglucitol (P < 0.0001). Conclusions Low C‐peptide levels have clinical significance and appear helpful in characterizing groups at‐risk for faster C‐peptide decline, complications, poorer metabolic control and severe hypoglycaemia. Low C‐peptide levels may be a biomarker for characterizing at‐risk patients with Type 1 diabetes.